1973
DOI: 10.1007/bf02640524
|View full text |Cite
|
Sign up to set email alerts
|

Variations in total amino acid content of peanut meal

Abstract: The amino acid levels of oil-free peanut meal prepared from 16 varieties of peanuts that had 24-30% protein content of the kernels were examined. Nearly two-fold variations in the limiting essential amino acids (lysine, isoleucine, methionine, threonine, and valine) were found and are reported. Data for the remaining amino acids also are included. Utilization of these variations in amino acid composition should assist the development of peanut protein of improved quality. An analytical procedure to measure ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
1
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 7 publications
3
15
1
1
Order By: Relevance
“…35% of the amino acid profile; the only other amino acid that approached 10% was arginine (Table 2). These results are similar to amino acid profiles reported previously (Oupadissakoon et al, 1980;Pancholy et al, 1978;Young et al, 1973;Young, 1979). Significant differences were recorded for all amino acids.…”
Section: Figsupporting
confidence: 94%
See 3 more Smart Citations
“…35% of the amino acid profile; the only other amino acid that approached 10% was arginine (Table 2). These results are similar to amino acid profiles reported previously (Oupadissakoon et al, 1980;Pancholy et al, 1978;Young et al, 1973;Young, 1979). Significant differences were recorded for all amino acids.…”
Section: Figsupporting
confidence: 94%
“…Peanuts are a rich source of nonmeat protein and average between 22 and 30% protein (Pancholy et al, 1978;Young et al, 1973). Amino acid profiles of peanut are not well balanced, with certain essential amino acids occurring in limiting concentration when compared to FAO (1990) recommended levels.…”
Section: Figmentioning
confidence: 97%
See 2 more Smart Citations
“…Therefore, the biosynthesis of the glycerate-3-phosphate group of amino acids competed with the biosynthesis of all the other amino acids; the competition resulted to the very low concentrations of cysteine, serine, and glycine irrespective of the mineral ion treatment of the peanut ( Table 2). Analyses of total amino acid contents of 16 varieties of peanuts showed that ser, gly, and cys together were the lowest in concentration [49].…”
Section: Amino Acid Groupsmentioning
confidence: 99%